THE INFLUENCE OF MORAL MESSAGES IN THE QURAN ON THE SOCIAL BEHAVIOR OF MUSLIMS - Silvia Ekasari; Iwan Ridwan; Armizi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
The Qur'an, as the primary source of Islamic teachings, contains various moral messages aimed at directing the individual and social behavior of humanity. This study aims to explore the influence of moral messages in the Qur'an on social behavior in the context of contemporary Muslim society. Through a literature approach, the study identifies and analyzes Qur'anic moral values and their application in social life. The results show that moral values such as justice, patience, kindness, and cooperation taught in the Qur'an have great potential in shaping positive social behavior in Muslim societies. Social practices such as zakat and social care are tangible applications of these values, showing a significant influence on social solidarity and harmony. However, challenges such as divergent interpretations, cultural influences and socio-economic conditions affect the way these values are applied in real life. The findings call for a more integrative and contextual approach to understanding and applying the Qur'ānic moral messages in social practice